The Perception on the Implementation of ICT based Media in Teaching English at BTA 70 Course - Nurmaisa, Nurmaisa; Sujarwati, Iis; Sofyan, Dedi (Linguistic, English Education and Art (LEEA) Journal, 2023)
Teachers and students play a key role in the successful integration of ICT into learning English. ICT-based learning will only succeed if teachers and students have a positive attitude towards practice. In this context, an empirical picture of teacher-student perceptions is essential as a basis for integrating ICT into the learning process. The aims of this study are to explore and analyse students' and teachers’ perceptions, students and teachers’ challenges, and benefits for teaching and learning toward the use of ICT in Teaching English at BTA 70 course To explore and analyse students’ perceptions toward the use of ICT in Teaching English at BTA 70 course. This study was mixed method study. This study used survey research in conducting the research exactly cross-sectional survey. There are 416 students and 15 teachers who became samples in this study and to get the sample The writer used purposive random sampling. The writer used a questionnaire for collecting the data. They are closed ended questionnaires adopted in Chainda A. M (2011). The results of this research, the students’ perception showed there positive aspects for students such as making students can share information, enhance students’ learning, and doing science experiments safely, for negative aspects consuming students’ time and irrelevant information which students got on the internet. And students’ attitude showed the students agree the use of ICT is effective in learning. Then, The use of ICT gave students obstacles where the obstacles became the challenges for students itself. The challenges for the students themselves, irrelevant information and time management are challenges for the students in learning by using ICT. It can be concluded if there are benefits of ICT in the learning process. Such as, ICT helps the students to improve, and also the students can learn individually. Keywords: Benefits, BTA 70, Challenges, ICT Media, Perception